A LaAlO3-silicon carbide mesh porous material and its preparation method and application
LaAlO3-silicon carbide mesh porous material prepared by vacuum immersion-air spraying-in-situ sintering technology solves the problems of degradation of mechanical properties of silicon carbide ceramics at high temperatures and oxidation in high-temperature wet oxidation environments through the construction of a multi-layer structure, and achieves the improvement of the material's mechanical properties, oxidation resistance and high-temperature infrared radiation efficiency.
Patent Information
- Application Number
- CN202311037690.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-08-16
AI Technical Summary
The existing silicon carbide mesh porous ceramics have decreased mechanical properties at high temperatures and are prone to oxidation in high temperature wet oxidation environments, resulting in reduced radiation and mechanical properties.
The LaAlO3-silicon carbide mesh porous material was prepared by vacuum impregnation-air spraying-in-situ sintering technology. Through the construction of a multi-layer structure, including LaAlO3 coating, Al2O3 transition layer, silicon carbide framework layer and Al2O3 filling layer, the mechanical properties of the material and high-temperature oxidation resistance are improved.
The mechanical properties, water vapor oxidation resistance and high-temperature infrared radiation efficiency of LaAlO3-silicon carbide mesh porous material were significantly improved, and the pressure resistance of the room temperature reached 2.1 to 2.7MPa, and the radiation efficiency and heating efficiency of the burner were also improved.
Smart Images

Figure CN117069497B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of porous medium combustion, in particular to a LaAlO 3 -Silicon carbide mesh porous material and its preparation method and application. Background Art
[0002] Porous media combustion technology is the super-adiabatic stable combustion of gas fuel in a three-dimensional mesh porous medium. It has the characteristics of high combustion efficiency, ultra-low emissions and clean use of low calorific value fuels. It is widely used in high-temperature equipment combustion systems in metallurgy, chemical industry, building materials and automobile fields. It is of great significance to improve the utilization rate of fossil energy and reduce carbon emissions in my country.
[0003] Silicon carbide reticulated porous ceramics have become the most popular porous burner medium material due to their low thermal expansion coefficient, high thermal conductivity and radiation efficiency. At present, silicon carbide reticulated porous ceramics are mostly prepared by organic foam impregnation method, which is made by impregnating ceramic slurry with organic foam and then sintering at high temperature. However, at high temperature, the organic foam decomposes to produce a large amount of gas, forming a large number of defects and hollow pores on the surface of silicon carbide, resulting in a decrease in the mechanical properties of silicon carbide reticulated porous ceramics. In addition, a high-temperature wet oxidation environment will be formed during the service of the silicon carbide reticulated porous ceramic burner, causing severe oxidation of the silicon carbide porous ceramic, thereby greatly reducing the mechanical properties and high-temperature radiation efficiency of the burner. Therefore, improving the mechanical strength, antioxidant ability and infrared radiation performance of silicon carbide porous ceramics is the key to preparing high-performance high-temperature silicon carbide porous medium burners.
[0004] At present, technicians have conducted in-depth research and technical development to solve the problems of poor mechanical properties and oxidation resistance of silicon carbide reticular porous ceramics: for example, patent CN107399989B: "A method for preparing silicon carbide-alumina composite foam ceramics" discloses a method for preparing silicon carbide-alumina composite foam ceramics by organic foam impregnation method, introducing low melting point oxides into silicon carbide-alumina composite foam ceramics, and forming ceramic microcrystals in situ to strengthen silicon carbide-alumina composite foam ceramics. This technology promotes the oxidation of SiC components in the raw materials and SiO 2 and Al 6 Si 2 O 13 The in-situ formation of ceramic microcrystals can improve the strength of silicon carbide-alumina composite foam ceramics. However, the composite ceramics prepared by this technology cannot resist the corrosion of high temperature wet oxidation environment, and the SiO 2It will also significantly reduce the high-temperature radiation performance of the ceramic. For example, patent CN101555161A "A surface modification method for improving the high-temperature oxidation resistance of silicon carbide foam ceramics" discloses that silicon carbide foam ceramics are pre-oxidized in a clean oxidizing atmosphere, and then replaced with a clean inert atmosphere for heat preservation without cooling. This method forms a stable crystalline SiO on the surface of the silicon carbide foam ceramic. 2 The protective film effectively inhibits the transmission of oxygen into the pores and plays a good role in oxidation protection. 2 The protective film reduces the high temperature radiation performance of the ceramic, and this method fails to improve the mechanical properties of the foamed ceramic. Therefore, there is an urgent need for a technical solution to simultaneously improve the high temperature radiation performance and mechanical properties of silicon carbide mesh porous ceramics. Summary of the invention
[0005] The object of the present invention is to provide a LaAlO 3 -Silicon carbide mesh porous material and its preparation method and application.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a LaAlO 3 -A method for preparing a silicon carbide mesh porous material, comprising the following steps:
[0008] (1) impregnating the polyurethane sponge in slurry I and then calcining to obtain a preform;
[0009] (2) impregnating the preform in slurry II and then calcining to obtain an intermediate;
[0010] (3) Spraying lanthanum-based slurry on the surface of the intermediate and then calcining to obtain the LaAlO 3 - Silicon carbide porous mesh material.
[0011] Preferably, the slurry I in step (1) comprises the following components in parts by weight:
[0012] 70-90 parts of silicon carbide, 5-15 parts of aluminum oxide, 5-15 parts of silicon powder, 1.2-2.5 parts of carboxymethyl cellulose, 0.2-0.5 parts of ammonium polycarboxylate and 25-45 parts of water.
[0013] Preferably, the immersion time in step (1) is 10 to 30 minutes;
[0014] The target temperature of the calcination is 800-900° C., the heating rate of the calcination is 1-3° C. / min, and the holding time after reaching the target temperature is 0.5-3 h.
[0015] Preferably, the slurry II in step (2) comprises the following components in parts by weight:
[0016] 90-110 parts of aluminum oxide, 0.2-0.5 parts of ammonium polycarboxylate and 20-40 parts of water.
[0017] Preferably, the immersion pressure in step (2) is 500-2500 Pa, and the immersion time is 5-30 min;
[0018] The target temperature of the calcination in step (2) is 1100-1350° C., the heating rate of the calcination is 2-5° C. / min, and the holding time after reaching the target temperature is 2-4 hours.
[0019] Preferably, the lanthanum-based slurry in step (3) is prepared from raw materials comprising the following weight fractions:
[0020] 60-65 parts of lanthanum oxide, 15-25 parts of aluminum oxide, 5-10 parts of titanium dioxide, 5-10 parts of strontium carbonate, 5-10 parts of manganese carbonate, 50-70 parts of ethanol, 1-5 parts of carbon source, 75-95 parts of solvent, and 60-80 parts of water.
[0021] Preferably, the carbon source is one or more of starch, dextrin, asphalt, polyvinyl alcohol and polyethylene glycol;
[0022] The solvent comprises polyvinyl alcohol and water, and the mass ratio of the polyvinyl alcohol to water is 3-7:90-100.
[0023] Preferably, the target temperature of the calcination in step (3) is 800-900°C, the heating rate of the calcination is 1-3°C / min, and the holding time after reaching the target temperature is 0.5-3h.
[0024] The present invention also provides LaAlO obtained by the preparation method 3 - Silicon carbide porous mesh material.
[0025] The present invention also provides the LaAlO 3 -Application of silicon carbide mesh porous materials in porous media combustion.
[0026] The present invention has the following beneficial effects:
[0027] The present invention provides a LaAlO 3 - A method for preparing a silicon carbide mesh porous material, comprising the following steps: impregnating a polyurethane sponge in a slurry I and then calcining to obtain a preform; impregnating the preform in a slurry II and then calcining to obtain an intermediate; spraying a lanthanum-based slurry on the surface of the intermediate and then calcining to obtain the LaAlO 3-Silicon carbide mesh porous material. The present invention adopts vacuum impregnation-air spraying-in-situ sintering technology, which has a simple preparation process and low cost. On the basis of pre-sintering the preform, the slurry II is infiltrated into the silicon carbide pore ribs through a vacuum impregnation process, and part of the slurry is attached to the surface of the silicon carbide pore ribs. After high-temperature in-situ sintering, the lanthanum-based slurry is sprayed on the surface of the intermediate body to construct a four-layer structure of high-performance silicon carbide composite pore ribs (including LaAlO 3 Coating, Al 2 O 3 Transition layer, silicon carbide skeleton layer and Al 2 O 3 Filling layer), these layers work synergistically to improve the LaAlO 3 -Mechanical properties, high-temperature water vapor oxidation resistance and high-temperature infrared radiation efficiency of silicon carbide mesh porous materials.
[0028] After vacuum impregnation, the silicon carbide mesh porous ceramic intermediate forms a filling layer and a continuous and dense transition layer after high-temperature reaction sintering. 2 O 3 The transition layer can effectively prevent LaAlO 3 - Silicon carbide mesh porous material during use 2 O(g) / O 2 (g) Penetration into the material, thereby improving the ability to resist water vapor corrosion. At the same time, the triangular holes generated by the decomposition of the polyurethane template in the porous ceramic are 2 O 3 The filling layer improves the compressive strength of the mesh porous material and improves the LaAlO 3 -Mechanical properties and water vapor oxidation resistance of silicon carbide mesh porous materials.
[0029] Sr doped 2+ , Mn 2+ and Ti 4+ After that, LaAlO 3 The lattice of the coating is distorted, the symmetry of the lattice structure is reduced, and the LaAlO 3 The lattice vibration absorption in the infrared region increases the concentration of hole carriers in the valence band, thereby increasing the LaAlO 3 The energy absorption of infrared light can improve the infrared emissivity. At the same time, the present invention introduces a micron-sized carbon source into the lanthanum-based slurry, which will produce micropores after heat treatment. When the aperture of the micropores is close to the near-infrared wavelength, the effect of multiple absorption of infrared light can be achieved, thereby further improving the infrared emissivity. In addition, Sr / Mn / Ti doped LaAlO 3After that, it will cause the change of the valence state and activity of Mn ions and Ti ions, generate oxygen defects, increase the relative content of surface adsorbed oxygen and the lattice oxygen migration rate; because the adsorbed oxygen can directly participate in the process of catalytic methane combustion, thus improving the Sr / Mn / Ti doped LaAlO 3 The catalytic activity of LaAlO 3 -The lean combustion limit, infrared emissivity and catalytic performance of silicon carbide mesh porous materials promote the complete combustion of methane in the porous ceramics and reduce the generation of harmful gases.
[0030] The present invention provides LaAlO obtained by the preparation method 3 -Silicon carbide mesh porous material has good mechanical properties, excellent resistance to water vapor corrosion, high high-temperature infrared radiation efficiency, and a room temperature compressive strength of 2.1 to 2.7 MPa.
[0031] The present invention provides the LaAlO 3 -Application of silicon carbide mesh porous material in porous medium burner. After testing, the LaAlO prepared by the present invention 3 - Silicon carbide mesh porous material is applied to porous medium burners, with a radiation efficiency of 80-95% at 1200-1350°C and a heating efficiency of 30-43°C / min; CO, NO x The emission is reduced from 140-160ppm and 0.6ppm to 10-20ppm and 0-0.2ppm respectively; and it can catalyze the combustion of methane with a concentration of 4vol%. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The LaAlO prepared in Example 1 3 -SEM image of the pore-rib fracture of silicon carbide mesh porous material; 1 is LaAlO 3 coating, 2 is the transition layer, 3 is the silicon carbide skeleton, 4 is Al 2 O 3 Filling layer;
[0033] Figure 2 The LaAlO prepared in Example 1 3 -SEM image of the pore surface of silicon carbide mesh porous material;
[0034] Figure 3 The LaAlO prepared in Example 1 3 -Local SEM image of pores in silicon carbide mesh porous material. DETAILED DESCRIPTION
[0035] The present invention provides a LaAlO 3-A method for preparing a silicon carbide mesh porous material, comprising the following steps:
[0036] (1) impregnating the polyurethane sponge in slurry I and then calcining to obtain a preform;
[0037] (2) impregnating the preform in slurry II and then calcining to obtain an intermediate;
[0038] (3) Spraying lanthanum-based slurry on the surface of the intermediate and then calcining to obtain the LaAlO 3 - Silicon carbide porous mesh material.
[0039] In the present invention, the slurry I in step (1) preferably comprises the following components in parts by weight:
[0040] 70-90 parts of silicon carbide, 5-15 parts of aluminum oxide, 5-15 parts of silicon powder, 1.2-2.5 parts of carboxymethyl cellulose, 0.2-0.5 parts of ammonium polycarboxylate and 25-45 parts of water.
[0041] In the present invention, the mass fraction of the silicon carbide is preferably 75 to 85 parts, more preferably 78 to 82 parts, and even more preferably 79 to 81 parts.
[0042] In the present invention, the mass fraction of the aluminum oxide is preferably 7 to 13 parts, more preferably 9 to 11 parts, and even more preferably 9.5 to 10.5 parts.
[0043] In the present invention, the mass fraction of the silicon powder is preferably 7 to 13 parts, more preferably 9 to 11 parts, and even more preferably 9.5 to 10.5 parts.
[0044] In the present invention, the mass fraction of the carboxymethyl cellulose is preferably 1.5 to 2.2 parts, more preferably 1.6 to 2.1 parts, and even more preferably 1.8 to 1.9 parts.
[0045] In the present invention, the mass fraction of the polycarboxylic acid ammonium is preferably 0.3 to 0.4 parts, more preferably 0.32 to 0.38 parts, and even more preferably 0.34 to 0.36 parts.
[0046] In the present invention, the mass fraction of water is preferably 30 to 40 parts, more preferably 32 to 38 parts, and even more preferably 34 to 36 parts.
[0047] In the present invention, the average particle size of the silicon powder is preferably ≤0.5 μm, more preferably ≤0.4 μm, and more preferably ≤0.3 μm.
[0048] The present invention also provides a method for preparing slurry I, comprising the following steps:
[0049] After silicon carbide, aluminum oxide and silicon powder are uniformly mixed, the remaining components are added and stirred to obtain slurry I.
[0050] In the present invention, the stirring speed is preferably 200-400 r / min, more preferably 250-350 r / min, more preferably 280-320 r / min, and the stirring time is preferably 30-60 min, more preferably 35-55 min, more preferably 40-50 min.
[0051] In the present invention, after the impregnation in step (1), the preform is pressed by rollers, dried, and then calcined in step (1) to obtain the preform.
[0052] In the present invention, the impregnation time in step (1) is preferably 10 to 30 minutes, more preferably 15 to 25 minutes, and more preferably 18 to 22 minutes; the drying temperature is preferably 90 to 110°C, more preferably 95 to 105°C, and more preferably 98 to 102°C; the drying time is preferably 12 to 24 hours, more preferably 15 to 20 hours, and more preferably 16 to 18 hours; the target temperature of the calcination is preferably 800 to 900°C, more preferably 820 to 880°C, and more preferably 840 to 860°C; the heating rate of the calcination is preferably 1 to 3°C / min, more preferably 1.5 to 2.5°C / min, and more preferably 1.8 to 2.2°C / min; the holding time after reaching the target temperature is preferably 0.5 to 3 hours, more preferably 1 to 2.5 hours, and more preferably 1.5 to 2 hours.
[0053] In the present invention, the slurry II in step (2) preferably comprises the following components in parts by weight: 90 to 110 parts of aluminum oxide, 0.2 to 0.5 parts of ammonium polycarboxylate, and 20 to 40 parts of water.
[0054] In the present invention, the mass fraction of the aluminum oxide is preferably 92 to 108 parts, more preferably 94 to 106 parts, and even more preferably 98 to 102 parts.
[0055] In the present invention, the mass fraction of the polycarboxylic acid ammonium is preferably 0.25 to 0.45 parts, more preferably 0.3 to 0.4 parts, and even more preferably 0.34 to 0.36 parts.
[0056] In the present invention, the mass fraction of water is preferably 25 to 35 parts, more preferably 28 to 32 parts, and even more preferably 29 to 31 parts.
[0057] The present invention also provides a method for preparing the slurry II, comprising the following steps:
[0058] The slurry II is obtained by mixing the above raw materials in different mass fractions and then ball milling.
[0059] In the present invention, the ball milling rate is preferably 200-400 r / min, more preferably 250-350 r / min, more preferably 280-320 r / min; the ball milling time is preferably 2-4 h, more preferably 2.5-3.5 h, more preferably 2.8-3.2 h.
[0060] In the present invention, after the impregnation in step (2), centrifugation and drying are performed, and then calcination in step (2) is performed to obtain the intermediate.
[0061] In the present invention, the impregnation pressure in step (2) is preferably 500-2500Pa, more preferably 1000-2000Pa, more preferably 1200-1800Pa, the impregnation time is preferably 5-30min, more preferably 15-20min, more preferably 17-18min; the centrifugal speed is preferably 50-70r / min, more preferably 55-65r / min, more preferably 58-62r / min; the centrifugal time is preferably 30s-90s, more preferably 40-80s, more preferably 50-70s; the drying temperature is preferably 90-110°C, more preferably 95-105°C, more preferably 98-102°C, the drying time is preferably 12-24h, more preferably 15-20h, more preferably 17-18h.
[0062] In the present invention, the target temperature of the calcination in step (2) is preferably 1100-1350°C, more preferably 1150-1300°C, and more preferably 1200-1250°C. The heating rate of the calcination is preferably 2-5°C / min, more preferably 3-4°C / min, and more preferably 3.2-3.8°C / min. The holding time after reaching the target temperature is preferably 2-4h, more preferably 2.5-3.5h, and more preferably 2.8-3.2h. After the calcination is completed, the furnace is cooled to room temperature to obtain a silicon carbide network porous intermediate.
[0063] In the present invention, the silicon carbide mesh porous ceramic after vacuum impregnation forms a filling layer and a continuous and dense transition layer after high temperature reaction sintering. 2 O 3 The transition layer can effectively prevent LaAlO 3 - Silicon carbide mesh porous material during use 2 O(g) / O 2 (g) Penetration into the material, thereby improving the ability to resist water vapor corrosion. At the same time, the triangular holes generated by the decomposition of the polyurethane template in the porous ceramic are 2 O 3The filling layer improves its room temperature compressive strength, achieving a synergistic improvement of LaAlO 3 -Mechanical properties of silicon carbide mesh porous materials and their resistance to water vapor oxidation.
[0064] In the present invention, the lanthanum-based slurry in step (3) is prepared from the following raw materials in parts by weight: 60-65 parts of lanthanum oxide, 15-25 parts of aluminum oxide, 5-10 parts of titanium dioxide, 5-10 parts of strontium carbonate, 5-10 parts of manganese carbonate, 50-70 parts of ethanol, 1-5 parts of carbon source, 75-95 parts of solvent, and 60-80 parts of water.
[0065] In the present invention, the mass fraction of the lanthanum oxide is preferably 61 to 64 parts, more preferably 62 to 63 parts, and even more preferably 62.4 to 62.6 parts.
[0066] In the present invention, the mass fraction of the aluminum oxide is preferably 16 to 24 parts, more preferably 17 to 23 parts, and even more preferably 19 to 21 parts.
[0067] In the present invention, the mass fraction of the titanium dioxide is preferably 6 to 9 parts, more preferably 6.5 to 8.5 parts, and even more preferably 7 to 8 parts.
[0068] In the present invention, the mass fraction of the strontium carbonate is preferably 6 to 9 parts, more preferably 6.5 to 8.5 parts, and even more preferably 7 to 8 parts.
[0069] In the present invention, the mass fraction of the manganese carbonate is preferably 6 to 9 parts, more preferably 6.5 to 8.5 parts, and even more preferably 7 to 8 parts.
[0070] In the present invention, the mass fraction of the ethanol is preferably 55 to 65 parts, more preferably 57 to 63 parts, and even more preferably 59 to 61 parts.
[0071] In the present invention, the mass fraction of the carbon source is preferably 1.5 to 4.5 parts, more preferably 2 to 3 parts, and even more preferably 2.4 to 2.6 parts.
[0072] In the present invention, the mass fraction of the solvent is preferably 80 to 90 parts, more preferably 82 to 88 parts, and even more preferably 84 to 86 parts.
[0073] In the present invention, the mass fraction of water is preferably 65 to 75 parts, more preferably 67 to 73 parts, and even more preferably 69 to 71 parts.
[0074] In the present invention, the carbon source is preferably one or more of starch, dextrin, asphalt, polyvinyl alcohol and polyethylene glycol.
[0075] In the present invention, the average particle size of the starch, dextrin or asphalt is independently preferably ≤2.5 μm, further independently preferably ≤2.0 μm, and even more independently preferably ≤1.5 μm.
[0076] In the present invention, the solvent preferably comprises polyvinyl alcohol and water, and the mass ratio of the polyvinyl alcohol to water is preferably 3-7:90-100, more preferably 4-6:92-98, and more preferably 4.5-5.5:94-96.
[0077] The present invention also provides a method for preparing the solvent, comprising the following steps:
[0078] The solvent is obtained by mixing polyvinyl alcohol and water and heating them in a water bath.
[0079] In the present invention, the water bath heating temperature is preferably 90-100°C, more preferably 92-98°C, more preferably 94-96°C, and the water bath heating time is preferably 90-120 min, more preferably 95-115 min, more preferably 100-105 min.
[0080] The present invention also provides a method for preparing the lanthanum-based slurry, comprising the following steps:
[0081] (a) mixing lanthanum oxide, aluminum oxide, titanium dioxide, strontium carbonate and manganese carbonate, adding ethanol, and sequentially ball milling, drying and calcining to obtain a mixed powder;
[0082] (b) After mixing the mixed powder and the carbon source, a solvent and water are added and ball milled to obtain the lanthanum-based slurry.
[0083] In the present invention, the ball milling rate in step (a) is preferably 200-400 r / min, more preferably 250-350 r / min, more preferably 280-320 r / min, the ball milling time is preferably 2-4 h, more preferably 2.5-3.5 h, more preferably 2.8-3.2 h; the drying temperature is preferably 90-110 ° C, more preferably 95-105 ° C, more preferably 98-102 ° C, the drying time is preferably 12-24 h, more preferably 12-24 h. The calcination temperature is preferably 1400-1500°C, more preferably 1420-1480°C, more preferably 1440-1460°C, the heating rate of the calcination is preferably 1-3°C / min, more preferably 1.5-2.5°C / min, more preferably 1.8-2.2°C / min, and the holding time to reach the calcination temperature is preferably 2-3h, more preferably 2.2-2.8h, more preferably 2.4-2.6h.
[0084] In the present invention, the ball milling rate in step (b) is preferably 200-400 r / min, more preferably 250-350 r / min, more preferably 280-320 r / min, and the ball milling time is preferably 2-4 h, more preferably 2.5-3.5 h, more preferably 2.7-3.3 h.
[0085] In the present invention, the lanthanum-based slurry is sprayed in step (3) and then dried, and calcined in step (3) to obtain the LaAlO 3 - Silicon carbide porous mesh material.
[0086] In the present invention, the amount of the slurry sprayed is preferably 8 to 12 g / m 2 , more preferably 9 to 11 g / m 2 , more preferably 10g / m 2 ; The spraying rate is preferably 0.5-3.5 m / min, more preferably 1-3 m / min, more preferably 1.5-2.5 m / min; the drying temperature is preferably 90-110°C, more preferably 92-108°C, more preferably 94-106°C, and the drying time is preferably 12-24h, more preferably 15-20h, more preferably 17-18h.
[0087] In the present invention, the target temperature of the calcination in step (3) is preferably 800-900°C, more preferably 820-880°C, and more preferably 840-860°C. The heating rate of the calcination is preferably 1-3°C / min, more preferably 1.5-2.5°C / min, and more preferably 1.8-2.2°C / min. The holding time after reaching the target temperature is preferably 0.5-3h, more preferably 1-2.5h, and more preferably 1.5-2h.
[0088] The present invention also provides LaAlO obtained by the preparation method 3 - Silicon carbide porous mesh material.
[0089] The present invention also provides the LaAlO 3 -Application of silicon carbide mesh porous materials in porous media combustion.
[0090] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0091] Example 1
[0092] 75 parts by weight of silicon carbide, 15 parts by weight of alumina powder, and 10 parts by weight of silicon micropowder were uniformly mixed, and then 1.3 parts by weight of carboxymethyl cellulose, 0.3 parts by weight of ammonium polycarboxylate, and 25 parts by weight of water were added, and then stirred at a rate of 60 r / min for 30 minutes to obtain slurry I, wherein the average particle size of the silicon micropowder was 0.5 μm;
[0093] 90 parts of alumina powder, 0.3 parts of ammonium polycarboxylate and 30 parts of water were mixed and ball-milled at a rate of 300 r / min for 2 h to prepare slurry II;
[0094] Mix 5 parts by weight of polyvinyl alcohol and 95 parts by weight of water, and heat in a water bath at 90° C. for 90 minutes to prepare a solvent;
[0095] 60 parts by mass of lanthanum oxide, 15 parts by mass of aluminum oxide, 5 parts by mass of titanium dioxide, 10 parts by mass of strontium carbonate and 10 parts by mass of manganese carbonate are mixed, 50 parts by mass of ethanol are added, the mixture is ball-milled at a rate of 350 r / min for 2 hours, and then dried at a temperature of 90°C for 12 hours. The mixture is heated to 1500°C at a rate of 1°C / min and kept warm for 3 hours to obtain a mixed powder; 3 parts by mass of starch, 80 parts by mass of solvent and 70 parts by mass of water are added to the mixed powder, and the mixture is ball-milled at a rate of 300 r / min for 2 hours to obtain a lanthanum-based slurry; wherein the average particle size of the starch is 2.5 μm.
[0096] The polyurethane sponge was immersed in the slurry I for 10 minutes and then rolled, and then dried at 90°C for 12 hours, and then heated to 850°C at a rate of 1°C / min, and then kept warm for 1 hour to obtain a preform;
[0097] The preform was immersed at a pressure of 500 Pa for 10 minutes, centrifuged at a speed of 60 r / min for 1 minute, dried at a temperature of 90°C for 12 hours, heated to 1300°C at a speed of 2°C / min in an air atmosphere, and kept at this temperature for 3 hours to obtain an intermediate;
[0098] Spray 10g / m on the surface of the intermediate at a rate of 2m / min 2 After the amount of lanthanum-based slurry was prepared, it was dried at 90°C for 12 hours, and the temperature was increased to 850°C at a rate of 1°C / min, and kept at this temperature for 1 hour to obtain the LaAlO 3 - Silicon carbide porous mesh material.
[0099] After testing (GBT 5072-2008): the LaAlO prepared in this example 3-The room temperature compressive strength of silicon carbide mesh porous material is 2.5MPa; the radiation efficiency of the porous medium burner at 1300℃ is 83%; the heating efficiency of the porous medium burner is 34℃ / min; the CO and NOx emissions of the porous medium burner are reduced from 150ppm and 0.6ppm to 18ppm and 0.2ppm respectively; the porous medium burner can catalyze the combustion of methane with a concentration as low as 4vol%.
[0100] The LaAlO prepared in Example 1 3 -Silicon carbide mesh porous material is observed under SEM electron microscope, and its pore-rib fracture SEM is as follows Figure 1 As shown, the SEM morphology of the hole-rib surface is as follows Figure 2 As shown, the local SEM image of the hole reinforcement is as follows Figure 3 As shown, from Figures 1 to 3 It can be seen that the prepared porous material has an obvious four-layer structure of coating-transition layer-skeleton-filling layer. 3 The coating improves the high temperature infrared radiation performance of the material. 2 O 3 The transition layer improves its resistance to water vapor oxidation.
[0101] Example 2
[0102] 80 parts by weight of silicon carbide, 15 parts by weight of alumina powder, 5 parts by weight of silicon micropowder, 1.3 parts by weight of carboxymethyl cellulose, 0.3 parts by weight of ammonium polycarboxylate and water were mixed and stirred at a rate of 60 r / min for 40 minutes to prepare slurry I, wherein the average particle size of the silicon micropowder was 0.5 μm;
[0103] 100 parts of alumina powder, 0.3 parts of ammonium polycarboxylate and 30 parts of water were mixed and ball-milled at a rate of 300 r / min for 2.5 h to prepare slurry II;
[0104] Mix 5 parts by weight of polyvinyl alcohol and 95 parts by weight of water, and heat in a water bath at 95° C. for 100 minutes to prepare a solvent;
[0105] 60 parts by weight of lanthanum oxide, 15 parts by weight of aluminum oxide, 5 parts by weight of titanium dioxide, 10 parts by weight of strontium carbonate and 10 parts by weight of manganese carbonate were mixed, 60 parts by weight of ethanol were added, the mixture was ball-milled at 350 r / min for 2.5 hours, and then dried at 100°C for 15 hours, and kept at 1500°C for 3 hours at a rate of 2°C / min to obtain a mixed powder; 3 parts by weight of dextrin, 80 parts by weight of solvent and 70 parts by weight of water were added to the mixed powder, and the mixture was ball-milled at 300 r / min for 2 hours to obtain a lanthanum-based slurry; wherein the average particle size of the dextrin is 2.5 μm;
[0106] The polyurethane sponge was immersed in the slurry I for 10 minutes and then rolled and dried at 100°C for 15 hours, and then heated to 850°C at a rate of 2°C / min and then kept warm for 1 hour to obtain a preform;
[0107] The preform was immersed at a pressure of 1000 Pa for 10 minutes, centrifuged at a rate of 60 r / min for 1 minute, dried at a temperature of 100° C. for 15 hours, heated to 1300° C. at a rate of 2° C. / min in an air atmosphere, and kept at this temperature for 3 hours to obtain an intermediate;
[0108] Spray 10g / m on the surface of the intermediate at a rate of 2m / min 2 After the amount of lanthanum-based slurry was prepared, it was dried at 90°C for 12 hours, and the temperature was increased to 850°C at a rate of 2°C / min, and kept at this temperature for 1 hour to obtain the LaAlO 3 - Silicon carbide porous mesh material.
[0109] After testing, the LaAlO prepared in this example 3 -The room temperature compressive strength of silicon carbide mesh porous material is 2.8MPa; the radiation efficiency of the porous medium burner at 1300℃ is 89%; the heating efficiency of the porous medium burner is 38℃ / min; the CO and NOx emissions of the porous medium burner are reduced from 150ppm and 0.6ppm to 15ppm and 0.1ppm respectively; the porous medium burner can catalyze the combustion of methane with a concentration as low as 4vol%.
[0110] Example 3
[0111] 90 parts by weight of silicon carbide, 5 parts by weight of alumina powder, 5 parts by weight of silicon micropowder, 1.3 parts by weight of carboxymethyl cellulose, 0.3 parts by weight of ammonium polycarboxylate and 25 parts by weight of water were mixed and stirred at a rate of 60 r / min for 30 minutes to prepare slurry I, wherein the average particle size of the silicon micropowder was 0.5 μm;
[0112] 90 parts of alumina powder, 0.3 parts of ammonium polycarboxylate and 30 parts of water were mixed and ball-milled at a rate of 300 r / min for 2 h to prepare slurry II;
[0113] Mix 5 parts by weight of polyvinyl alcohol and 95 parts by weight of water, and heat in a water bath at 105° C. for 110 minutes to prepare a solvent;
[0114] 60 parts by weight of lanthanum oxide, 15 parts by weight of aluminum oxide, 5 parts by weight of titanium dioxide, 10 parts by weight of strontium carbonate and 10 parts by weight of manganese carbonate were mixed, and then 50 parts by weight of ethanol were added, and the mixture was ball-milled at a rate of 350 r / min for 2 hours, and then dried at a temperature of 90°C for 12 hours, and kept at a temperature of 1500°C for 3 hours at a rate of 1°C / min to obtain a mixed powder; 3 parts by weight of starch, 80 parts by weight of solvent and 70 parts by weight of water were added to the mixed powder, and the mixture was ball-milled at a rate of 300 r / min for 2 hours to obtain a lanthanum-based slurry; wherein the average particle size of the starch is 2.5 μm;
[0115] The polyurethane sponge was immersed in the slurry I for 30 minutes and then rolled and dried at 90°C for 12 hours, and then heated to 850°C at a rate of 1°C / min and then kept warm for 1 hour to obtain a preform;
[0116] The preform was immersed at a pressure of 2500Pa for 30min, centrifuged at a speed of 60r / min for 1min, dried at a temperature of 90°C for 12h, heated to 1300°C at a speed of 2°C / min in an air atmosphere, and kept at this temperature for 3h to obtain an intermediate;
[0117] Spray 10g / m on the surface of the intermediate at a rate of 2m / min 2 After the amount of lanthanum-based slurry was prepared, it was dried at 90°C for 12 hours, and the temperature was increased to 850°C at a rate of 1°C / min, and kept at this temperature for 1 hour to obtain the LaAlO 3 - Silicon carbide porous mesh material.
[0118] After testing, the LaAlO prepared in this example 3 -The room temperature compressive strength of silicon carbide mesh porous material is 2.9MPa; the radiation efficiency of the porous medium burner at 1300℃ is 95%; the heating efficiency of the porous medium burner is 42℃ / min; the CO and NOx emissions of the porous medium burner are reduced from 150ppm and 0.6ppm to 10ppm and 0.1ppm respectively; the porous medium burner can catalyze the combustion of methane with a concentration as low as 4vol%.
[0119] Comparative Example 1
[0120] The only difference is that no carbon source is added, and the remaining steps are the same as Example 1.
[0121] After testing: LaAlO prepared in this comparative example 3 -The room temperature compressive strength of silicon carbide mesh porous material is 2.8MPa; the radiation efficiency of the porous medium burner at 1300℃ is only 75%; the heating efficiency of the porous medium burner is 28℃ / min; the CO and NOx emissions of the porous medium burner are reduced from 150ppm and 0.6ppm to 72ppm and 0.4ppm respectively.
[0122] Comparative Example 2
[0123] The only difference is that lanthanum oxide, aluminum oxide, calcium carbonate and chromium oxide are not added, and the remaining steps are the same as those in Example 2.
[0124] After testing: LaAlO prepared in this comparative example 3 -The room temperature compressive strength of silicon carbide mesh porous material is 2.7MPa; the radiation efficiency of the porous medium burner at 1300℃ is only 72%; the heating efficiency of the porous medium burner is 25.5℃ / min; the CO and NOx emissions of the porous medium burner are reduced from 150ppm and 0.6ppm to 63ppm and 0.3ppm respectively.
[0125] It can be seen from the above embodiments that the present invention provides a LaAlO 3 - A method for preparing a silicon carbide mesh porous material, comprising the following steps: impregnating a polyurethane sponge in a slurry I and then calcining to obtain a preform; impregnating the preform in a slurry II and then calcining to obtain an intermediate; spraying a lanthanum-based slurry on the surface of the intermediate and then calcining to obtain the LaAlO 3 -Silicon carbide mesh porous material. The present invention adopts vacuum impregnation-air spraying-in-situ sintering technology, which has a simple preparation process and low cost. On the basis of pre-sintering the preform, the slurry II is infiltrated into the silicon carbide pore ribs through a vacuum impregnation process, and part of the slurry is attached to the surface of the silicon carbide pore ribs. After high-temperature in-situ sintering, the lanthanum-based slurry is sprayed on the surface of the intermediate body to construct a four-layer structure of high-performance silicon carbide composite pore ribs (including LaAlO 3 Coating, Al 2 O 3 Transition layer, silicon carbide skeleton layer and Al 2 O 3 Filling layer), these layers work synergistically to improve the LaAlO 3 -Mechanical properties, high-temperature water vapor oxidation resistance and high-temperature infrared radiation efficiency of silicon carbide mesh porous materials.
[0126] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a LaAlO3-silicon carbide mesh porous material, characterized in that: It includes the following steps: (1) impregnating the polyurethane sponge in slurry I and then calcining to obtain a preform; (2) impregnating the preform in slurry II and then calcining to obtain an intermediate; (3) spraying lanthanum-based slurry on the surface of the intermediate and then calcining to obtain the LaAlO3-silicon carbide mesh porous material; The slurry I in step (1) comprises the following components in parts by weight: 70-90 parts of silicon carbide, 5-15 parts of aluminum oxide, 5-15 parts of silicon powder, 1.2-2.5 parts of carboxymethyl cellulose, 0.2-0.5 parts of ammonium polycarboxylate and 25-45 parts of water; The slurry II in step (2) comprises the following components in parts by weight: 90-110 parts of aluminum oxide, 0.2-0.5 parts of ammonium polycarboxylate and 20-40 parts of water; The lanthanum-based slurry in step (3) is prepared from raw materials comprising the following weight fractions: 60-65 parts of lanthanum oxide, 15-25 parts of aluminum oxide, 5-10 parts of titanium dioxide, 5-10 parts of strontium carbonate, 5-10 parts of manganese carbonate, 50-70 parts of ethanol, 1-5 parts of carbon source, 75-95 parts of solvent, and 60-80 parts of water.
2. The preparation method according to claim 1, characterized in that The immersion time in step (1) is 10 to 30 minutes; The target temperature of the calcination is 800-900°C, the heating rate of the calcination is 1-3°C / min, and the holding time after reaching the target temperature is 0.5-3h.
3. The preparation method according to claim 1, characterized in that: The immersion pressure in step (2) is 500-2500 Pa, and the immersion time is 5-30 min; The target temperature of the calcination in step (2) is 1100-1350°C, the heating rate of the calcination is 2-5°C / min, and the holding time after reaching the target temperature is 2-4h.
4. The preparation method according to claim 1, characterized in that: The carbon source is one or more of starch, dextrin, asphalt, polyvinyl alcohol and polyethylene glycol; The solvent comprises polyvinyl alcohol and water, and the mass ratio of the polyvinyl alcohol to water is 3-7:90-100.
5. The preparation method according to claim 1, 2 or 4, characterized in that: The target temperature of the calcination in step (3) is 800-900°C, the heating rate of the calcination is 1-3°C / min, and the holding time after reaching the target temperature is 0.5-3h.
6. The LaAlO3-silicon carbide network porous material obtained by the preparation method according to any one of claims 1 to 5.
7. Use of the LaAlO3-silicon carbide mesh porous material according to claim 6 in porous medium combustion.
Citation Information
Patent Citations
Surface modification method for enhancing high-temperature oxidation resistance of silicon carbide foam ceramic
CN101555161A
A method for preparing reinforced silicon carbide-alumina composite foam ceramics
CN107399989B
Far-infrared energy-saving radiation coating for high-temperature furnace
CN111004029A
Cordierite-silicon carbide reticular porous material for porous medium combustion and preparation method thereof
CN114874014A